Diabetic neuropathy and painful diabetic neuropathy in the Middle East and North Africa (MENA) region: Much work needs to be done. Issue 4 (August 2016) - Petropoulos, Ioannis N.; Javed, Saad; Azmi, Shazli; Khan, Adnan; Ponirakis, Georgios; Malik, Rayaz A.
الملخص: يُظهر انتشار الاعتلال العصبي السكري، والاعتلال العصبي السكري المؤلم في الشرق الأوسط وشمال أفريقيا تباينا كبيرا. ويعكس ذلك الأساليب التشخيصية المختلفة المستخدمة لتشخيص الاعتلال العصبي, وكذلك تنوع المجموعات السكانية قيد الدراسة، واختيار المجموعات من مراكز العناية الأولية والثانوية. إن علاج الاعتلال العصبي السكري في حد ذاته غير كاف, وينعكس ذلك من سوء التحكم في عوامل الخطورة مثل التحكم في السكر وضغط الدم والدهون في هذه المنطقة, الذي يُترجم بدوره إلى نِسَبٍ عالية من الإصابة بتقرحات القدم والبتر. بالنسبة لعلاج الأعراض, فإن التوصيات المبنية على التجارب التي أجريت في الغرب هي بلا شك التي يُوصَى بها لعلاج سكان الشرق الأوسط. بالتأكيد فإن الخصائص السكانية واستجابة المرضى من ناحية نجاعة العلاج والأضرار الجانبية مختلفة. وتحتاج إلى تجارب سريرية محلية. هناك اعتماد مبالغ فيه على صرف فيتامينات "ب" بدعوى أنها تحفز إصلاح الأعصاب. مع وجود أدلة على تخفيف الأعراض العصبية عند استخدام كلا من فيتامين "ب" و "د", نكرر بأن التجارب السريرية في هذه المنطقة، لا بد منها لترسيخ دورهما في علاج الاعتلال العصبي السكري والاعتلال العصبي السكري المؤلم. Abstract: The prevalence of diabetic peripheral neuropathy and painful diabetic peripheral neuropathy in the Middle East shows huge variability. This reflects the differing diagnostic techniques employed to diagnose neuropathy, but also the heterogeneity of the populations studied and the selection of populations from primary and secondary care. The treatment of diabetic neuropathy per se is inadequate as reflected by the poor control of risk factors such as glucose control, blood pressure and lipids in this region, which translates into the high rates of foot ulceration and amputation. In relation to symptomatic treatment, recommendations based on trials conducted in the West are without question, endorsed for the treatment of populations in the Middle East. Surely the demographics and patient responses both in terms of efficacy and side effects differ and therefore warrant local clinical trials. There is an over reliance on the prescription of B vitamins with the claim that they induce nerve repair. Whilst there is evidence for the relief of neuropathic symptoms with both vitamin B and D, again clinical trials are required in this region to establish their role in the treatment of diabetic neuropathy and painful diabetic neuropathy.